Green IT: Sustainability as a Competitive Factor in the IT Market - Almeida, Luís Fernando; Souza, Victor Hugo Lara; da Cruz, Pedro Augusto Simões; dos Reis, Felipe Kauan; Soares, Liziane Santos (Anais do Workshop de Sistemas de Informação (WSIS), 2024)
The growing demand for sustainability has led the Information Technology (IT) sector to adopt Green IT practices, which aim to minimize the environmental impact caused by the use of technological resources. This article explores the concept of Green IT and its importance as a competitive factor in the IT market, where energy efficiency and sustainable resource management are becoming strategic advantages. Based on a literature review, we will analyze how the adoption of sustainable practices can impact the economic performance of companies, generating not only operational savings but also enhancing corporate visibility and image. This article aims to present the relevance of the Green IT concept in the current IT context and highlight how the integration of sustainability into IT strategies can be a catalyst for innovation and a crucial competitive advantage in today’s landscape. Additionally, gaps in the literature and possible future directions for the field will be discussed.